Recruitment, experience, and retention among women with HIV and hazardous drinking participating in a clinical trial - Shantrel S. Canidate; Christa L. Cook; Deepthi Varma; Giselle D. Carnaby; Nicole Ennis; Nichole E. Stetten; Robert L. Cook (BMC, 2020)
Abstract Background Despite efforts by the NIH to enhance the participation of women and minorities in clinical research, women with HIV continue to remain underrepresented in alcohol intervention research. The purpose of this study is to better understand the reasons why women with HIV and hazardous drinking participated in the WHAT-IF? study and to discuss their experience (positive or negative) in the study. The WHAT-IF? study was a randomized clinical trial that evaluated pharmacotherapy for a reduction in drinking among women with HIV. Methods Convenience and theoretical sampling were used to recruit women with HIV and hazardous drinking to complete qualitative interviews. These women had previously completed a clinical alcohol intervention trial and had consented to be contacted in the future for study-related purposes. The biopsychosocial model was used to frame the interview questions that assessed multiple determinants of drinking behavior and helped explain linkages to broader health constructs. Results A total of 20 women with HIV and hazardous drinking completed the qualitative interview. Several factors were identified by the women as influential in their decision to participate in the WHAT-IF? study, such as the ability to quit or reduce their drinking to nonhazardous levels (biological), the ability to gain knowledge or a greater understanding of the negative effects of hazardous drinking on HIV disease progression (psychological), and peer pressure and monetary compensation (social). Also, the women identified factors (positive or negative) associated with their clinical trial experience, such as the effects of the study medication on the woman's body (biological), thoughts and feelings toward study procedures (i.e. medication, lab work, study assessments) and the length of the study (psychological), and the interactions with the WHAT-IF? study staff (social). Conclusion Recruiting and retaining women with HIV in alcohol intervention research remains a challenge. Findings from this study suggest that women with HIV who are hazardous drinkers may benefit from participating in research studies that could help them to reduce or quit their drinking, increase their knowledge about specific behavior changes, and earn monetary compensation. Also, positive staff interactions may be instrumental in retaining minority women in alcohol intervention research.